THE EFFECT OF PROFITABILITY, COMPANY SIZE, LIQUIDITY, AND ASSETS STRUCTURE ON CAPITAL STRUCTURED IN LQ45 INDEX MANUFACTURING ISSUERS IN THE INDONESIA STOCK EXCHANGE IN 2014-2019 - Krisanta Sumardi Putra; Matrodji H. Mustafa (Dinasti International Journal of Education Management And Social Science, 2021)
The purpose of this research is to prove the effect of profitability, company size, liquidity, and asset structure on the capital structure of manufacturing issuers in LQ45 in IDX in 2014- 2019. The study analyzed four free variables using secondary data in panel data with eight company cross-sections and a six-year time series. Analysis method used in the form of regression of panel data with random effect method. The results showed that profitability (ROE) has a positive and significant effect on the capital structure (DER), company size (SIZE) positively and significantly affect the capital structure (DER). , liquidity (CR) positively and significantly affect the capital structure (DER), asset structure (AS) positively but insignificantly affect the capital structure (DER) and profitability (ROE), company size (SIZE), liquidity (CR) and asset structure (AS) simultaneously influence the capital structure by 87.1496%, In comparison the remaining 12.8504% was explained by other independent variables that were not studied.